3D Cloud Rendering Visualization based on Nuclear Power Industrial Internet. Issue 1 (1st April 2022) - Zhang, Fan; Zhang, Hao; Luo, Ying; Xu, Kui
Abstract: Industrial Internet is a new generation of information and communication technology, which is a deep integration of industrial economy with new infrastructure, application mode and industrial ecology. As the development of nuclear power industry, it raises many demands on the use of industrial internet. China National Nuclear Power has been devoted to constructing the Nuclear Power Industrial Internet since 2018. Many of its business and process needs 3D visualizationto demonstrate the real-time operating data. Therefore, a cloud rendering technical proposal is designed to realize this purpose. The configuration and working flow of the cloud rendering are described in detail. Finally, a use-case is applied to verify the technical proposal. Some future work for improvement is given.